Consensus on Recommended Functions of a Smart Home System to Improve Self-Management Behaviors in People With Heart Failure: A Modified Delphi Approach - Islam, Sheikh Mohammed Shariful; Nourse, Rebecca; Uddin, Riaz; Rawstorn, Jonathan C.; Maddison, Ralph (Frontiers in Cardiovascular Medicine, 2022)
Background Smart Home systems could enhance clinical and self-management of heart failure but evidence to guide the design of Smart Home system functionalities is lacking. Objective To identify consensus-based recommendations for functions of a Smart Home system for people living with heart failure. Methods Healthcare professionals caring for people living with heart failure participated in a two-round modified Delphi survey and a consensus workshop. Survey Round 1 consisted of 30-items, grouped into eight categories, based on international guidelines. Participants rated item importance (9-point Liket scale) and suggested new functions. Survey Round 2 asked panel members to re-rate items where consensus was not reached, and rate new items. Consensus agreement was defined a priori as ≥70% of respondents rating a score of ≥7 and ≤15% rating a score ≤3. Panel members were invited to an online consensus workshop to discuss items that had not reached consensus after Round 2. Results In Round 1, 15 experts agreed 24/30 items were ‘very important’, and suggested six new items. In Round 2, experts agreed 2/6 original items and 6/6 new items were very important’. During the consensus workshop, experts endorsed 2/4 remaining items. Conclusion Using Deplhi methodology, we identified core functions of a Smart Home system to support self-care in people living with heart failure. Next steps involve co-design and protyping solutions with consumers and healthcare providers to achieve these core functions.